Analisis Kebijakan Penghentian Bantuan Amerika Serikat Terhadap United Nations Relief And Works Agency For Palestine Refugees (UNRWA) - Herse, Firsto Farisky; Yusra, Muhammad; Irawan, Poppy (Palito, 2025)
This study aims to analyze a United States foreign policy that suspends its foreign aid to the United Nations Relief and Works Agency for Palestine Refugees in the Near-East (UNRWA). Historically, the United States has long been a country that consistently provides foreign aid to UNRWA. Until the Donald Trump administration, US foreign aid to UNRWA was stopped. Joe Biden as the next president-elect took a different policy by returning US foreign aid to the humanitarian agency for Palestine. However, after the October 7, 2023 attack on Israel, the Joe Biden administration issued a policy to stop all US foreign aid to UNRWA. The researcher assumes that there are other goals besides those conveyed by the United States government that underlie this policy. This study was analyzed using the theory of foreign policy analysis with descriptive analysis method. This research found that the purpose of the United States government in stopping its foreign aid to UNRWA was a political effort by the United States to suppress all forms of criticism and acts of struggle and resistance from the Palestinian people against the oppression and colonization carried out by Israel.